Implementasi Pembelajaran Kontekstual Di Sekolah Alam Bengawan Solo - Rahmawati, Afifah Luhur; , Murfiah Dewi Wulandari, S.Psi.,M.Psi Psikolog (2017)
In the learning process, the main task of a teacher is to teach, educate, train students to achieve velofntelligence, character heights, and optimal skills. Teachers are a key element in improving the quality of education to become an intelligent, skilled, and character community. In fact, teachers in teaching and learning activities in the lassroom tend to use traditional learning strategies. This means that the teacher transforms his knowledge by using lecture method so that the learning is centered on the teacher. Teaching and learning activities should be student-centered, which means students should be more actively digging their own information. The purpose of this research is: (1) Todescribe the teacher in implementing contextual learning in learning at Bengawan Solo Nature School (SABS). (2) To describe the obstacles in implementing contextual learning in Bengawan Solo School of Nature (SABS). (3) To describe solutions to overcome obstacles in the implementation of ntextuallearning in Bengawan Solo School of Nature (SABS). In this study, the subjects of the research were class 1, 2, 3, and 4. Then the data collection technique was using interview, observation, and documentation. This type of research is qualitative research. Informants in this research are principal 1, 2, 3, and 4 and grade 3 students. Data are analyzed through data reduction measures, data presentation, conclusions.Technique of examination of data validity is done by triangulation technique and source. The results showed that: (1) The teachers at the Bengawan Solo School of Nature have applied contextual learning quite well. (2) Obstacles faced by teachers at Bengawan Solo School of Nature in implementing contesktual learning include: there are still teachers who are over time during the lesson, there are still students who feel bored and difficult to manage the learning time. (3) The solution of teachers to overcome obstacles in implementing contextual learning in Bengawan Solo School of Nature, among others: still pay attention to the allocation of learning time that has been determined from the overnment so that the learning objectives are well achieved, teacher's clever to give different activities To students but still in the same context.